Truncated tau deregulates synaptic markers in rat model for human tauopathy - Jadhav, Santosh; Katina, Stanislav; Kovac, Andrej; Kazmerova, Zuzana; Novak, Michal; Zilka, Norbert (Frontiers in Cellular Neuroscience, 2015)
Synaptic failure and neurofibrillary degeneration are two major neuropathological substrates of cognitive dysfunction in Alzheimer’s disease (AD). Only a few studies have demonstrated a direct relationship between these two AD hallmarks. To investigate tau mediated synaptic injury we used rat model of tauopathy that develops extensive neurofibrillary pathology in the cortex. Using fractionation of cortical synapses, we identified an increase in endogenous rat tau isoforms in presynaptic compartment, and their mis-sorting to the postsynaptic density. Truncated transgenic tau was distributed in both compartments exhibiting specific phospho-pattern that was characteristic for each synaptic compartment. In the presynaptic compartment, truncated tau was associated with impairment of dynamic stability of microtubules which could be responsible for reduction of synaptic vesicles. In the postsynaptic density, truncated tau lowered the levels of neurofilaments. Truncated tau also significantly decreased the synaptic levels of Aβ40 but not Aβ42. These data show that truncated tau differentially deregulates synaptic proteome in pre- and postsynaptic compartments. Importantly, we show that alteration of Aβ can arise downstream of truncated tau pathology.